European Idea of Higher Education Area: Bologna Declaration – Expectations and Actions - Pociūtė, Birutė (Acta Paedagogica Vilnensia, 2002)
European cultural dimensions. This implies: developing a Europe of knowledge, strengthening of stable, peaceful and democratic societies; enhancing mobility in employment and study; implementing the Bologna Magna Charta Universitatum 1988. In short the Declaration focuses on the promotion of co-operation and international competitiveness of European higher education. There are expectations of national reforms: the changes in two-tier degree structures, shorter first degrees, bridges between university and non-university sectors and external evaluation. At the institutional level, the reforms should also be considered to shape the curriculum development and evaluations (mare professionally relevant, more international and mare multidisciplinary). The article focuses on the universities role to facilitate study and labour mobility. Identifying labour needs calls for a constant update of the curriculum. The question is whether universities should move to professional training instead of providing an academic education. The article is dealing with the difficulties of the implementation of Bologna Declaration: a tension between academic education and professional training, between equality and opportunity, between internationalization and globalisation and etc. Mass higher education and life-long learning cannot be uniform across individuals, communities and countries. Reality is different in many universities, but the changes are needed in many universities too.